Neuro-emotions based on electroencephalograph response to different color Ardisia mamillata Hance plants in elderly people with and without cognitive impairment - Du, Juan; Chen, Xiaomei; Li, Xi; Pan, Yuanzhi; Fu, Erkang; Huang, Yumei; Zhu, Chunyan; Jiang, Mingyan; Hassan, Ahmad; Wu, Dingru; Ma, Jun; Yuan, Guangsheng (Frontiers in Public Health, 2022)
Background: The aims of this study were twofold: (1) to assess the difference of neural emotion based on EEG from the cognitively impaired elderly(CNE) and the cognitively normal elderly (CIE) participants viewing different colors Ardisia mamillata Hance ; and (2) to determine which color Ardisia mamillata Hance has greater benefits for boosting their neuro-emotions. Methods: The cognitive function of the participants was judged by using the revised Chinese version of the mini-mental state examination(MMSE) scale combined with the daily cognitive performance of the participants, 10 CNE volunteers and 10 CIE volunteers were recruited as participants for this study. Two varieties of Ardisia mamillata Hance, Green Tiger Tongue (GTT) with green leaves and Red Tiger Tongue (RTT) with reddish brown leaves, were observed as plant materials. Six emotional indexes, including stress, engagement, interest, excitement, focus and relaxation, were then measured by electroencephalo-graph (EEG). Results: RTT had the most positive effect on EEG neural emotion in the CNE group, with significant reductions in stress, engagement, and focus in the RTT test,. While the combination of GTT+RTT had the positive effect on EEG neuro-emotions. in the CIE group, with significant reductions in engagement and focus in the GTT +RTT test. There was not any statistically significant differences for the interest, excitement and relaxation index from the CNE and CIE participants in all tests. Conclusion: The significant reductions in stress, engagement, and focus value of CIE in the RTT test, which indicated that the CNE participants were more relaxed . RTT is reddish-brown and warm color plant, so, that CNE individuals should always have the warm color plants indoors or outdoors, which could help boost their neural emotions. While significant reductions in engagement and focus vale of CIE participants in the GTT +RTT test, which indicited that the CIE participants were more relaxed. The combination of GTT+RTT are the combination cold and warm color plant, therefor, the CIE individuals should always have the combination of cool and warm colors plants indoors or outdoors, which could help boost their EEG neuro-emotions. Keywords: EEG, Neuro-emotion, Plant color, Ardisia mamillata Hance, elderly, cognitive impairment